The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2016
DOI: 10.1007/s11242-016-0722-y
|View full text |Cite
|
Sign up to set email alerts
|

Asymmetry Characteristics of Oil Production by Spontaneous Imbibition from Cores with Two Ends Open

Abstract: Spontaneous imbibition experiments with two ends open (TEO) boundary condition showed that oil production from each open face of core is asymmetrical while the invasion of water is symmetrical. Investigating the asymmetry characteristics of oil production is helpful to understand the imbibition displacement mechanisms. In this paper, a mathematical model considering the difference in capillary back pressure for TEO imbibition is established by assuming piston-like advance of the imbibition front. Based on the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 34 publications
0
4
0
Order By: Relevance
“…This is because the characteristic length is calculated based on the assumption of cores’ isotropy. In actual experiments, due to the different pore diameters of the cores’ imbibition surface and different capillary pressures, the imbibition speed of each end surface is asymmetric . Lyu et al .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…This is because the characteristic length is calculated based on the assumption of cores’ isotropy. In actual experiments, due to the different pore diameters of the cores’ imbibition surface and different capillary pressures, the imbibition speed of each end surface is asymmetric . Lyu et al .…”
Section: Resultsmentioning
confidence: 99%
“…In actual experiments, due to the different pore diameters of the cores' imbibition surface and different capillary pressures, the imbibition speed of each end surface is asymmetric. 51 Lyu et al 52 carried out similar experiments using tight sandstone. They found that under the TEO boundary conditions, the conclusion is similar.…”
Section: Influence Of Cementitious Mineralsmentioning
confidence: 99%
“…However, asymmetry in oil production under TEO is observed, and this ambiguous behavior cannot be explained through the assumption that oil will be evenly displaced by SI from the two ends with a no-flow boundary at the middle of the core. Meng et al indicated that the difference in capillary back pressure of the two ends of the core can cause asymmetrical oil production. The capillary back pressure is related to the pore size at the open faces of the sample, which may differ in the same core .…”
Section: Resultsmentioning
confidence: 99%
“…During the soaking process, fracturing fluid is imbibed into the reservoir and displaces the oil therein, thereby enhancing oil recovery. In fractured reservoirs, due to the randomness of the fracture morphology, the contact modes and contact areas between the fracturing fluid and rock are different, thus forming different boundary conditions. ,, Generally, the boundary conditions of cores are divided into all-faces-open (AFO), one-end-closed (OEC), two-ends-closed (TEC), two-ends-open (TEO), and one-end-open (OEO). , Among them, the researches on OEC boundary condition has not received much attention. In addition to boundary conditions, the parameters that affect the imbibition characteristics also include core size, porosity, permeability, fluid surface tension, viscosity, and so on.…”
Section: Introductionmentioning
confidence: 99%